The Challenges of Applying Communicative Language Teaching in Indonesian Senior High School Context - Sholihah, Hidayatus (ENCOUNTER, 2012)
Thinking about a solution of the main problem faced by Indonesian students in learning English communicatively, CLT might be a good one. CLT is proved as an effective approach that can solve the problem of many language learners who can not communicate in English fluenty after learning English for several years. This article analyzes the challenges to apply CLT approach successfully in Indonesia as one of EFL ( English as Foreign Language) contexts. First, issues of theoretical assuption on CLT such as: what should be the roles of teachers and students in CLT, what type of materials and activities in the CLT classroom are discussed. Then, how English teachers and the students in Indonesia play their roles in CLT classroom?, do they have the difficulties in playing their roles ?, do the teachers can set the classroom that can encourage students to communicate in English by using CLT classroom activities and materials? are analyzed. The finding shows that applying CLT is still challenging in Indonesian school context because both teachers and students still can not play their roles well. In addition, CLT activities such as role play and games can not be applied in the classroom effectively yet. Then, authentic materials is still rare and teachers are struggling to access them. Finally, teacher training, improving classroom facilities and reforming English testing system at Indonesian schools are the solutions suggested in this article to apply CLT successfully in Indonesian school context.